Gender, credit, and firm outcomes - Delēs, Manthos D.,Hasan, Iftekhar,Iosifidi, Maria,Ongena, Steven (Swiss Finance Institute, 2019)
Small and micro enterprises are usually majority owned by entrepreneurs. Using a unique sample of loan applications from such firms, we study the role of owners' gender in the credit decision of banks and the post-credit decision firm outcomes. We find that, ceteris paribus, female entrepreneurs are more prudent loan applicants, with both the probabilities to apply for credit and of firm default after the loan origination being smaller. However, the relatively more aggressive behavior of male applicants pays off in terms of higher average firm performance after the loan origination
10.2139/ssrn.3469613
Keywords: Graue Literatur; Frauen; Geschlechterunterschiede; Kreditgeschäft; Kreditrisiko; Unternehmenserfolg; EU-Staaten; Gender; Loan application; Bank's credit decision; Firm performance